2020
DOI: 10.1101/2020.04.28.067132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteasome activator PA200 maintains stability of histone marks during transcription and aging

Abstract: The epigenetic inheritance relies on stability of histone marks, but various diseases, including aging-related diseases, are usually associated with alterations of histone marks. How the stability of histone marks is maintained still remains unclear. The core histones can be degraded by the atypical proteasome, which contains the proteasome activator PA200, in an acetylation-dependent manner during somatic DNA damage response and spermiogenesis.Here we show that PA200 promotes the transcription-coupled degrada… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Such association of acetylated histones with open regions of the chromatin can perhaps account for their susceptibility to degradation. Indeed, the degradation of acetylated histones by PA200-capped proteasomes was suggested to be coupled to transcription, and to affect the stability of the total populations of histone variant H3.3 and core histone H4, probably during histone exchange [24]. Yet, it is still unclear what initiates this process and to what extent PA200 plays an active part in it.…”
Section: Accepted Articlementioning
confidence: 99%
See 3 more Smart Citations
“…Such association of acetylated histones with open regions of the chromatin can perhaps account for their susceptibility to degradation. Indeed, the degradation of acetylated histones by PA200-capped proteasomes was suggested to be coupled to transcription, and to affect the stability of the total populations of histone variant H3.3 and core histone H4, probably during histone exchange [24]. Yet, it is still unclear what initiates this process and to what extent PA200 plays an active part in it.…”
Section: Accepted Articlementioning
confidence: 99%
“…For example, under normal conditions, the arginine methyl transferase PRMT1 mediates symmetrical dimethylation of H4 on arginine in position 3 (H4R3me2as), which maintains histone H4 stability. Exposure of cells to oxidative stress, DNA damage, or hyperoncogenic signaling pressure (associated with senescence) leads to a reduction in PRMT1-mediated H4R3me2, promoting the ubiquitin-independent degradation of H4 by PA200-capped proteasomes [23,75]. Degradation of H4 thereby reduces nucleosomal occupancy and affects cell proliferation by promoting the transcription of cell cycle inhibitors, senescence-associated genes, and regulators of apoptosis [75].…”
Section: Ubiquitin-independent Proteasomal Degradation Of Histonesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the sirtuin family of proteins, which is related to many aging-related physiological processes, can work with proteins such as p53, NF-kB, forkhead box O, PGC-1, and mTOR to regulate the stress response and thus affect the aging process. Han Xia et al [14] reported that PA200-proteasome could maintain the stability of histone code by mediating the histone degradation process. The histone acetyltransferase encoded by gene KAT7 [15], which was discovered last year, also belongs to class III.…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 99%